PENGARUHÂ PERMAINANÂ TRADISIONALÂ GOBAKÂ SODORÂ TERHADAPÂ PERKEMBANGANÂ MOTORIKÂ KASARÂ DANÂ Â SIKAPÂ KOOPERATIFÂ ANAKÂ TKÂ KELOMPOKÂ BÂ DIÂ KECAMATANÂ SIDOARJOÂ - erdiana, lita (Pedagogi : Jurnal Anak Usia Dini dan Pendidikan Anak Usia Dini, 2016)
ABSTRACT ThisÂ  studyÂ  aimsÂ  toÂ  determineÂ  theÂ  influenceÂ  ofÂ  theÂ  traditionalÂ  gameÂ  gobakÂ  sodor againstÂ grossÂ motorÂ developmentÂ andÂ cooperativeÂ attitudeÂ kindergartenÂ childrenÂ inÂ group BÂ inÂ theÂ districtÂ ofÂ Sidoarjo. ThisÂ studyÂ isÂ basedÂ onÂ dataÂ inÂ theÂ fieldÂ indicatingÂ thatÂ aspectsÂ ofÂ grossÂ motorÂ skillsÂ of childrenÂ  lessÂ  exploitedÂ  wellÂ  andÂ  cooperativeÂ  attitudeÂ  ofÂ  childrenÂ  whoÂ  doÂ  notÂ  develop optimally.ThisÂ  researchÂ  isÂ  appliedÂ  inÂ  theÂ  formÂ  ofÂ  experimentsÂ  usingÂ  controlÂ  groups.Â  ThisÂ  study usesÂ aÂ designÂ pretestâ€posttestÂ controlÂ groupÂ designÂ withÂ oneÂ kindÂ ofÂ treatment.Â DataÂ were obtainedÂ fromÂ theÂ initialÂ observationÂ andÂ finalÂ observations. Â DataÂ  fromÂ  observationsÂ  obtained asÂ  follows:Â  TheÂ  averageÂ  resultsÂ  ofÂ  initial observationsÂ  experimentalÂ  groupÂ  isÂ  8.95.Â  WhileÂ  atÂ  theÂ  endÂ  ofÂ  theÂ  observationÂ  afterÂ  being treatedÂ  traditionalÂ  gamesÂ  gobakÂ  sodorÂ  averageÂ  yieldÂ  grossÂ  motorÂ  development experimentalÂ  groupÂ  isÂ  12.75.Â  GrossÂ  motorÂ  developmentÂ  inÂ  theÂ  controlÂ  groupÂ  the observationÂ  ofÂ  theÂ  initialÂ  (pretest)Â  anÂ  averageÂ  ofÂ  8.825.Â  WhileÂ  atÂ  theÂ  endÂ  ofÂ  the observationÂ  ofÂ  anÂ  averageÂ  yieldÂ  ofÂ  9.6Â  grossÂ  motorÂ  development.Â  TheÂ  averageÂ  resultsÂ  of theÂ  developmentÂ  ofÂ  socialÂ  behaviorÂ  inÂ  theÂ  experimentalÂ  groupÂ  theÂ  initialÂ  observation, namelyÂ  9.05.Â  AtÂ  theÂ  endÂ  ofÂ  theÂ  observationÂ  ofÂ  anÂ  averageÂ  ofÂ  12.3.Â  WhileÂ  theÂ  average results ofÂ  theÂ  developmentÂ  ofÂ  socialÂ  behaviorÂ  inÂ  theÂ  controlÂ  group:Â  9Â  fromÂ  theÂ  initial observationÂ andÂ theÂ observationÂ ofÂ theÂ endÂ ofÂ anÂ averageÂ 9.775 ANOVAÂ  testÂ  resultsÂ  obtainedÂ  asÂ  follows:Â  statisticalÂ  analysisÂ  ofÂ  dataÂ  grossÂ  motor developmentÂ  valueÂ  ofÂ  FÂ  =Â  31.778Â  isÂ  greaterÂ  thanÂ  FÂ  tableÂ  =Â  4.00Â  andÂ  statisticalÂ  analysisÂ  of socialÂ  behaviorÂ  developmentÂ  dataÂ  obtainedÂ  valueÂ  ofÂ  FÂ  =Â  19.837Â  isÂ  greaterÂ  thanÂ  FÂ  tableÂ  = 4.00 MutivariatÂ  TestÂ  resultsÂ  obtainedÂ  asÂ  follows:Â  theÂ  valueÂ  ofÂ  PÂ  valuesÂ  forÂ  fourÂ  different multivariateÂ  testÂ  onÂ  theÂ  traditionalÂ  gameÂ  gobakÂ  sodorÂ  overallÂ  lessÂ  thanÂ  0.05Â  isÂ  0.Â  With demikiam noÂ  significantÂ  influenceÂ  ofÂ  theÂ  independentÂ  variableÂ  onÂ  theÂ  dependentÂ  variable all BasedÂ  onÂ  theÂ  analysis,Â  itÂ  canÂ  beÂ  concludedÂ  thatÂ  theÂ  traditionalÂ  gameÂ  gobakÂ  sodor effectÂ onÂ grossÂ motorÂ developmentÂ andÂ socialÂ behaviorÂ ofÂ children. Â KeyWords:Â  TraditionalÂ GamesÂ GobakÂ Sodor,Â GrossmotorÂ skills,Â SocialÂ Behavior.